The politics of language in Ireland, 1366-1922 : a sourcebook - Crowley, Tony (Politics of language., 2000)
"For almost a thousand years language has been an important and contentious issue in Ireland. The story of the relations between the English and Irish languages is a complex one full of unexpected alliances, strange accounts of historical origins, and peculiar forms of cultural identity. Above all it reflects the great themes of Irish history: colonial invasion, native resistance, religious and cultural difference." "Collected here for the first time are texts on the politics of language from the date of the first legislation against Irish, the Statute of Kilkenny of 1366, to the constitution of the Free State in 1922. Crowley's introduction connects these texts to current debates, taking the Belfast Agreement as an example, and illustrates how the language debates continue to have historical resonance today. Divided into six historical sections with detailed introductions, this unique sourcebook includes familiar cultural texts such as Spenser's View of the Present State of Ireland and essays and letters by Yeats and Synge, alongside less familiar writings, from introductions to the first Irish-English and English-Irish dictionaries to the Preface to the New Testament in Irish (1602)." "Providing direct access to original texts, this is an historical resource book which can be used as a case study in the relations between language and cultural identity both in the present and the past."--Jacket